Creation and Implementation of Protected Areas and Recognition of OECMs Based in Sustainable Integrated Landscapes Approach. Attachment 1 and 2 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2024)
A project in Brazil for the creation and strengthening of protected areas in the Amazon region is described. It focuses on identifying priority areas for technical studies in order to propose the creation of new protected areas. Thirteen sites in five Amazonian states are mentioned, categorized according to threat level and land protection status. The project seeks to declare vast areas as protected areas and effective conservation measures, with the objective of achieving the designation of undesignated lands in the Amazon and achieving zero deforestation in the Amazon biome. It highlights the importance of recognizing and supporting effective area-based conservation measures, as well as the priority management of existing and newly declared protected areas to address emerging threats. The project is structured in three components: creation of protected areas, recognition of other effective area-based conservation measures, and support for protected area management. It mentions the need to address environmental and socioeconomic challenges in the region, with a focus on protecting biodiversity, ecosystems and local communities; the project will also address the need to protect the environment and local communities.